Biodegradation of squalene and n-hexadecane by Gordonia amicalis HS-11 with concomitant formation of biosurfactant and carotenoids - Sowani, Harshada; Deshpande, Ashish; Gupta, Vidya; Kulkarni, Mohan; Zinjarde, Smita (International Biodeterioration & Biodegradation, 2019)
Gordonia amicalis HS-11 has been enriched from a hydrocarbon contaminated tropical soil sample. The ability of this organism to utilize a triterpenic polyunsaturated hydrocarbon, squalene (2,6,10,15,19,23-hexamethyl-6,6,10,14,18,20-tetracosahexane) and the model saturated hydrocarbon n-hexadecane is described here. The isolate degraded squalene and n-hexadecane (79 +/- 3.02 and 96 +/- 4.11%, respectively) after eight days of incubation. The isolate produced an extracellular biosurfactant that reduced surface tension from 69 +/- 2.83 to 40 +/- 1.63 and 35 +/- 2.34 mN m(-1) with squalene and n-hexadecane as carbon sources, respectively, after 6 days. The Actinomycete cleaved squalene to geranylacetone and famesyl acetaldehyde that were further utilized for supporting growth. n-Hexadecane was degraded via monoterminal oxidation and activities of important enzymes (alkane hydroxylase and alcohol dehydrogenase) were highest (215 +/- 8.76 and 169 +/- 6.02 units mg(-1) protein, respectively) after four days. Cells grown on squalene were short and with n-hexadecane there were clumps of longer cells. Squalene and n-hexadecane-grown cell surfaces were smooth possibly due to extracellular surface active compounds. While growing on hydrophobic substrates, some cells were seen adhering to droplets and others were in the free form. The culture was able to simultaneously degrade hydrocarbons and produce two commercially relevant value-added products. The yield of the extracellular biosurfactant on n-hexadecane was 480 mg l(-1) and cells grown on squalene and n-hexadecane also yielded carotenoids (2.3 +/- 0.14 and 2.9 +/- 0.10 mg g(-1) dry cell weight, respectively). This is the first report on the utilization of squalene by Gordonia.
Keywords: Aerobic biodegradation; Carotenoids; Catabolic pathways; Emulsifier; Gordonia amicalis HS-11